2013
DOI: 10.1111/hae.12218
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C infection and outcomes in the Scottish haemophilia population

Abstract: Patients with bleeding disorders previously frequently became infected with hepatitis C virus. We identified the number of patients infected in Scotland and assessed several aspects of the outcomes of HCV infection and its treatment comparing these with cohorts infected for other reasons. We calculated the number of individuals infected in Scotland (cohort A) starting with the total number of patients treated in Scottish haemophilia centres registered on the UKHCDO database between 1970 and 1989. Cases were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Prior to these developments, the HCV and HBV infection rates in hemophilic patients in Poland were high (95% of those who were anti-HCV positive, 8.7% of HBsAg, and 68% of anti-HBc positive) (2), whereas the rates observed in the general population were significantly lower (anti-HCV was 0.6% - 2.1% and HBsAg was about 1%) (15-19). Our results were comparable with the rates observed among hemophiliacs in the USA and Western European countries (3, 4, 10, 20). …”
Section: Discussionsupporting
confidence: 89%
“…Prior to these developments, the HCV and HBV infection rates in hemophilic patients in Poland were high (95% of those who were anti-HCV positive, 8.7% of HBsAg, and 68% of anti-HBc positive) (2), whereas the rates observed in the general population were significantly lower (anti-HCV was 0.6% - 2.1% and HBsAg was about 1%) (15-19). Our results were comparable with the rates observed among hemophiliacs in the USA and Western European countries (3, 4, 10, 20). …”
Section: Discussionsupporting
confidence: 89%
“…22.9% of these patients with haemophilia spontaneously cleared HCV and the remainder developed chronic hepatitis C, which is similar to other reports. 3,9 Our cohort data confirmed the mild, slowly progressing course of chronic Our study is limited by its retrospective nature and data reported from only one referral centre. A relatively small number of patients were included, and the majority were male.…”
Section: Hepatitis C Infection In a Greek Population With Inherited Bsupporting
confidence: 68%
“…In Scotland, the total number of patients with bleeding disorders, infected with HCV, is estimated at 455; of these, 255 had a documented positive anti-HCV test, while 200 were assessed as probably infected [12] .…”
Section: Ijbpas February 2019 8(2)mentioning
confidence: 99%